PENDIDIKAN MULTIKULTURAL DALAM SURAT AL-HUJARAT AYAT 12-13 SIKAP ISLAM TERHADAP KERAGAMAN DAN PERDAMAIAN DUNIA - Basid, Abdul (El-Hamra, 2019)
Diversity was a sunatullah that must be accepted by all humans, even the awareness of differences in almost all aspects of life must be owned by Muslims, because Allah Who destined it. However, there are some Muslims who deny this diversity and make it a source of division not as mercy. So from that it is important to see the attitude of the al-Qur?an towards this diversity so that it becomes clearer and stronger of good understanding of differences, especially Surat al-Hujarat: 12-13 which are actually referred to the multicultural verses in the Qur'an. The method used is the interpretation of maudhu'i. The multicultural education used to analyze the verse and to look for the dimensions of content integration, knowledge construction, prejudice reduction, equal education and dimensions of empowering school culture and social structures. from systematics of academic thinking to Surat al-Hujarat: 12-13 there was a conception of multicultural education that obtained in the form of learning to live in difference, living with three mutual aspects which include mutual trust, mutual understanding, and mutual respect, living openly in thinking, living ful appreciation and interdependence, and instill conflict resolution and anti-violence in life.Key Words: al-Hujarat, Multicultural Education, Maudhu?i Interpretation